Sinergi Undang Undang TPKS dan Nilai-Nilai Sadd Adz-Dzari’ah Dalam Pencegahan Kekerasan Seksual Di Perguruan Tinggi - Setiawan, Beni; Erwin, Erwin; Sumantri, Aditiya Kusuma; Aditia, Fanita (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
Sexual violence in Indonesian higher education institutions has reached an alarming level, with 2,761 cases recorded in 2024, necessitating a comprehensive response from the perspectives of both national and Islamic law. This study analyzes the synergy between the Sadd adz-Dzari’ah principle in Islamic law and national legal policies, specifically Law Number 12 of 2022 concerning Crimes of Sexual Violence (TPKS Law) and Regulation of the Minister of Education, Culture, Research, and Technology Number 55 of 2024 concerning the Prevention and Handling of Violence in Higher Education Environments. This research employs a normative legal method utilizing statutory, conceptual, and normative-analytical approaches conducted through library research on primary and secondary legal materials. The findings indicate that the Sadd adz-Dzari’ah principle, which emphasizes the prevention of harm before it occurs, shares a philosophical convergence with the preventive approaches outlined in the TPKS Law and Permendikbudristek Number 55 of 2024. The legal maxims dar’u al-maf?sid muqaddam ’ala jalb al-ma??li? (warding off evil takes precedence over bringing about benefits) and al-wasa’il laha ahkam al-maqasid (means take the same ruling as their objectives) reinforce the legitimacy of proportional preventive policies without infringing upon the privacy rights of the academic community. This study recommends strengthening the harmonization between Islamic legal values and positive law to create safe campus environments through an approach of preventive ethics, proportional supervision, and privacy rights protection based on maqasid al-syariah